Recomendação de Conteúdo em Ambientes de Convergência Digital Incorporada ao Middleware Ginga - Vieira , Priscilla Kelly Machado; Lino, Natasha Queiroz (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2012)
The emerging scenario of interactive Digital TV (iDTV) is promoting the increase of interactivity in the communication process and also in audiovisual production, thus rising the number of channels and resources available to the user. This reality makes the task of finding the desired content becoming a costly and possibly ineffective action. The incorporation of recommender systems in the iDTV environment is emerging as a possible solution to this problem. This paper aims to propose an approach to content recommendation in iDTV, incorporated to the middleware Ginga, based on data mining clustering techniques and knowledge representation, considering the iDTV as a digital convergence environment (DTV and Web).